Fiacs Classroom Interaction Analysis of Teacher Talk in Teaching Narrative Text Using Android Media - Kurniadi, Didit; Suprapto, Suprapto (CV. Global Health Science Group, 2025)
Teacher talk is crucial for classroom engagement since it helps students better understand the topic and motivates them to participate actively in learning. Based on the framework of the Flanders Interaction Analysis Category System (FIACS) created by Flanders, this qualitative study seeks to assess the forms of talks used by the teacher in classroom interaction. The objective of this study is to analyze the types and frequency of teacher talk in an English classroom and to examine how these interactions influence student participation. The researcher used audio recordings, observation for two class meetings, and an interview with the teacher in the 10th grade of a senior high school in Semarang, Central Java, Indonesia, to gather the data. The topic of the teaching material was narrative. The teacher used Android as the media in teaching English. The findings indicated that all seven categories of teacher discussion were present. Giving instructions came first among the most used (38.53). It is followed by asking questions with 30 instances (27.52%), encouraging or praising with 11 instances (10.1%), lecturing with 13 instances (11.92%), criticizing or defending authority with five instances (4.6%), accepting or using the ideas of students with six instances (5.50%), and accepting feelings (1.83). The low response from the students caused the domination by the teacher.